(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this paper, an error-correcting LDPC code has been investigated and modeled to provide an increase in noise immunity in a digital television system of the DVB-T2 standard. The algorithm of functioning of the noise-correcting LDPC codec was studied theoretically and practically. The noisecorrecting LDPC code in the digital television system of the DVB-T2 standard with the developed interactive computer simulation program in the Matlab/Simulink programming language, the dependence of the number of errors on the error probability for the noise-correcting LDPC code was modeled and investigated.